Xenophon the Socratic Prince - Buzzetti, E. author. aut Link
XVII, 337 p. 1 illus.
Keywords: An interpretation of Xenophon's Anabasis of Cyrus, paralleling the text to Machiavelli's The Prince, and focusing on the question: How did the Socratic education help Xenophon reconcile morality with effectiveness, the noble with the good, as a ruler?